REMEDIASI MISKONSEPSI KONSEP CAHAYA PARA SISWA SMP MENGGUNAKAN PEMBELAJARAN ULANG BERBASIS MNEMONIC - Senja, Senja; Maria, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThis research aimed to describe the remediation of misconception of light’s concept effectivity of students of SMP PGRI 1 Paloh by mnemonic-based re-learning. The form of the research is pre-experimental with one group pretest-posttest design. This research involved 29 students of grade VIII A which were taken by using intact group technique. The tool of data collection used was a multiple-choice test with three alternative choices consist of 9 items. Based on the distribution of students which experienced misconception during pretest and posttest, it was found the average percentage was declining in the amount of 38,31%. McNemar test result in 6 items showed for db = 1 and while the binomial test result showed 2 items smaller than , so as a whole there was a significant change of conception toward the concept of light. The average of remediation effectivity using mnemonic-based re-learning for every concepts was 53 (category medium). The result of this research was expected to be an alternative when attempting to remediate the misconception the students were having. Keyword: Remediation, Misconception, Mnemonic, Light